Numerical Investigation on Ultimate Shear Strength of Diagonally Stiffened Steel Plate Shear Walls - Amr A. Elbanna, Sherif S. Safar, Mokhtar M. Seddiek (International Journal of Advanced Science and Technology, 2020)
This paper investigates the ultimate shear strength of diagonally stiffened steel plate shear walls (SPSWs) under seismic loads. The finite element method is utilized to simulate and analyze the seismic behavior and performance of SPSWs. Verification of the proposed finite element model has been executed by comparing its results with those obtained from the previous experimental tests published in the literature. Sequential studies are conducted to assess the effect of varying parameters (width, height, and thickness of the plate, number of floors, yield strength of frame and plate, area and inertia of top beam, and inertia of stiffeners) on the ultimate base shear carried by, individually, frame, and plate. Based on the outcomes of the parametric investigation, equations to obtain the ultimate base shear recommended by theory is upgraded. Two factors, ηp and ηf, are introduced on the theoretical base shear equations supported by the plate and frame, respectively. It is meanwhile to ensure that validation of all the proposed equations is also performed to evaluate the applicability of these modifications. The congruence or the small error found between the outcomes of the numerical modeling for the control and different models, and the proposed equations qualify the validation of the equations.